2012
DOI: 10.2147/ijn.s29819
|View full text |Cite
|
Sign up to set email alerts
|

Composite scaffolds of mesoporous bioactive glass and polyamide for bone repair

Abstract: A bone-implanted porous scaffold of mesoporous bioglass/polyamide composite (m-BPC) was fabricated, and its biological properties were investigated. The results indicate that the m-BPC scaffold contained open and interconnected macropores ranging 400-500 µm, and exhibited a porosity of 76%. The attachment ratio of MG-63 cells on m-BPC was higher than polyamide scaffolds at 4 hours, and the cells with normal phenotype extended well when cultured with m-BPC and polyamide scaffolds. When the m-BPC scaffolds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…We have chosen those materials because they are known to be used clinically and in research [42], [43], [44], [45], [46], [47]. All membranes were provided by Membrana and varied in their physical properties such as wall thickness and maximum pore size ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have chosen those materials because they are known to be used clinically and in research [42], [43], [44], [45], [46], [47]. All membranes were provided by Membrana and varied in their physical properties such as wall thickness and maximum pore size ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The obtained composite scaffolds showed increased mechanical strength up to 1 MPa compared to the pure silk reference material, formation of surface hydroxyapatite after 24 h and a high ALP activity [106]. Su et al used solvent casting and particulate leaching to fabricate MBG/polyamide scaffolds that exhibited excellent biocompatibility and osteoconductivity as well as more effective osteogenesis than the reference polyamide scaffold in vivo [107].…”
Section: Compositesmentioning
confidence: 99%
“…For instance, Shi et al and Yun et al reported the preparation of hierarchically MBG scaffolds by using the nonionic triblock copolymer and polyurethane as co-templates to achieve nanoporosity (<10 nm) and macro porosity (>100 lm) respectively, and their compressive modulus was less than 1 MPa [30][31][32]. As a solution, composites of biodegradable polymers (PCL, PLGA, alginate, collagen and so on) and MBG ceramics were developed to increase the mechanical stability [33,34]. In addition, an alternative 3D plotting method is developed to promote mechanical strength [35,36].…”
Section: Introductionmentioning
confidence: 99%